Respuesta :

snog

Answer:

0

Step-by-step explanation:

Since you didn't attach an image of the graph I'll have to do this the hard way.

x + 2y = 2  (1)

2x + 4y = -8 (2)

x + 2y = -4 (Divide equation (2) by 2)

0 = 6 (Subtract the third equation from the first)

Since 0 is not equal to 6 the answer is No Solutions.

Answer:

no solutions

Step-by-step explanation:

x+2y=2

2x+4y=−8​

Multiply the first equation by -2

-2x -4y = -4

Add this to the second equation

-2x-4y = -4

2x +4y = -8

--------------------------

0x+0y = -12

0 = -12

This is never true so there are no solutions

ACCESS MORE
EDU ACCESS